トウキョウ ショウワキチ カン ノ タンパ デンパン トクセイ - 長谷川, 貞雄; ハセガワ, サダオ; 竹内, 鉄雄; タケウチ, テツオ; 磯部, 武; イソベ, タケシ; HASEGAWA, Sadao; TAKEUCHI, Tetsuo; ISOBE, Takeshi (国立極地研究所, 1968)
P(論文) Measurements of the field intensity of 6055 KHz (NSB, Nippon Short Wave Broadcasting), 9595 KHz (NSB) and 15300 KHz (NHK, Radio Japan) were made at Syowa Station in Antarctica, from April 1966 to January 1967. Results were compared with the calculated values by the two methods developed by K. MIYA and CRPL (Central Radio Propagation Laboratory), and with the analized result by MIYA'S method on the whole It was found that the propagation of the recieved radio wave was always controlled by MUF (Maximum Usable Frequency) of the ionosphere at Syowa Station, and that the propagation was also made by the Es (Sporadic E) mode at near midnight in winter there Also, we found that the propagation of 9595 KHz had the best condition of all the frequencies measured thiough all seasons. departmental bulletin paper